Extratos de romã sobre inibição larval de Haemonchus spp e cooperia spp provenientes de bovinos - Dos Anjos, Carolina; Silva, Bruno Toledo; Holsback Silveira Fertonani, Luciane; Silva, Camile Sanches; Matsumoto, Leopoldo Sussumo; Da Silva, Regildo Márcio Gonçalves [UNESP]; De Mello-Peixoto, Erika Cosendey Toledo (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2016)
Consumers increasingly demand natural food and absent of toxic waste and medicated. The aim of this study was to evaluate the aqueous extract of dried and in natura stem from pomegranate on the larval inhibition of Haemonchus spp. and Cooperia spp. obtained from cattle. Dried and in natura aqueous extract from pomegranate stem (AEPS), negative control (autoclaved distilled water) and positive control (levamisole hydrochloride 0.05 mg / mL) were evaluated. Four mL of each treatment were used, and the results were evaluated in triplicate by egg counts per gram of feces (EPG), larval culture and counting of the larvae. The mean of the larvae that developed per gram of feces was submitted to logarithimic transformation log. (X + 10). The EPG had an average value of 3.620 eggs, identified in larval culture from Haemonchus spp. and Cooperia spp. Dried AEPS presented, by the reduction of larvae, effectiveness of 92.29% for Haemonchus spp. and 96.97% for Cooperia spp. In natura, this extract showed 80% of efficacy against Cooperia larvae, being considered moderately effective; however, for Haemonchus spp. this extract was not effective. These results are specially important for organic and agroecological systems of production, that not allow the use of chemical parasiticides. In conclusion, the use of dried AEPS showed potential anthelmintic and may represent important natural therapeutic option.
Pomegranate extracts on larval inhibition of Haemonchus spp and Cooperia spp obtained from cattle
Keywords: Agroecology; Medicinal plants; Punica granatum linn; Worm